MO-STUDIES OF ENZYME REACTION-MECHANISMS .1. MODEL MOLECULAR-ORBITAL STUDY OF THE CLEAVAGE OF PEPTIDES BY CARBOXYPEPTIDASE-A - Alex, Alexander; Clark, Timothy (Journal of Computational Chemistry, 1992)
Ab initio and semiempirical (AM1) molecular orbital theory has been used to model the cleavage of formamide at the active site of carboxypeptidase A. The model active site consists of a zinc dication coordinated to two imidazoles, an acetate, a water with a hydrogen-bonded formate, and a formamide molecule as model substrate. AM1 has been compared with ab initio theory for the coordination of water and formamide to Zn++ and found to give excellent energetic results. The course of the amide cleavage was therefore calculated with AM1. The first step of the reaction is the dissociation of the zine-coordinated water to give an active ZnOH+ species. The remote formate acts as proton acceptor. This process has an activation energy of only 4.6 kcal mol-1. The next and rate-determining step is the concerted addition of the ZnOH+ moiety to the formamide C=O bond. The Zn-0 distance in the transition state is more than 3 angstrom. In four further steps, the amide nitrogen is protonated and the C-N bond cleaved. The net activation energy for the entire process is 15.5 kcal mol-1 relative to the active site model and 19.6 kcal mol-1 relative to the most stable point on the calculated reaction profile.